Implementasi Metode Applied Behavior Analysis (Aba) dengan Media Flashcard untuk Meningkatkan Proses Belajar PAI Peserta Didik Autis - Maryanti, Maryanti; Fatimah, Siti (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2022)
This research aims to determine the improvement of the PAI learning process for autistic students at the Muhammadiyah 1 Karanganyar Kebumen elementary school through the ABA method with flashcard media. This research is Classroom Action Research (PTK) which was carried out over 2 cycles with 2 meetings in each cycle. The subjects in this research were 3 students with autism. The instruments used were observation sheets and interview sheets. Data validity using the triangulation technique. The research results show that there is an increase in PAI learning using the ABA (Applied Behavior Analysis) method assisted by flashcard media.